Effect of chip temperature during bonding on particleboard properties - İstek, Abdullah; Yiğittap, Özgür; Özlüsoylu, İsmail (Maderas. Ciencia y Tecnología, 2023)
In the production of particleboard, the chips emerging from the drying oven usually pass into the bonding process without sufficiently cooling down. Moreover, along with the effect of friction during the bonding process, the increased chip temperature boosts the consumption of resin/adhesive and affects the properties of the board. This study investigated the effect of chip temperature during the bonding process on the properties of particleboard. With this aim, the effects were determined for six different temperatures (25 °C, 30 °C, 35 °C, 40 °C, 50 °C, 55 °C) measured during the bonding of the chips. According to the results, optimum board properties were obtained from the groups in which the chip temperature measured during the bonding process was 30 °C – 40 °C. Furthermore, it was determined that chip temperatures of above 40 °C during the bonding process significantly reduced the mechanical properties.